PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI (STUDI PADA KARYAWAN KANTOR PUSAT POS SUMBAWA BESAR PT. POS INDONESIA) - Aminollah; Fitra Hasri Rosandi (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2020)
The research was conducted to determine the effect of job satisfaction on organizational commitment at the Sumbawa Besar Post head office, PT. Indonesian post. This research was aimed to reveal how far job satisfaction affects organizational commitment. This research uses a descriptive quantitative approach. The sampling technique used purposive sampling. The sample in this study was conducted by 14 permanent employees and staff who work at the head office of Pos Sumbawa Besar PT. Indonesian post. This research data uses two scales, namely the scale of job satisfaction and organizational commitment scale. The results showed that there was an effect of job satisfaction on organizational commitment with a significant value (Sig.) Of 0.01 less than 0.05, so the alternative hypothesis (Ha) was accepted. These results indicate that if job satisfaction is positive, the organizational commitment will increase. Job satisfaction has an effect of 58.9% while the other 41.1% is influenced by other variables not examined in this study.